Pengaruh Locus Of Control Dan Self Efficacy Terhadap Kinerja Pegawai UPTD KPHL Bukit Barisan - Khadri Arisya Putra; Aminar Sutra Dewi (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
Good performance is an employee who can complete work according to the specified target. Good performance is optimal performance. The employee's performance is capital for the agency to achieve its goals. This research aims to test the Locus of Control on employee performance, to test Self Efficacy on employee performance, the sampling method uses a total sampling technique of 41 samples, using normality testing and multiple regression. The research results show that Locus of Control has a positive and significant effect on employee performance. Self Efficacy does not have a significant effect on employee performance.